Implications of the just energy transition for employees in the South African coal mining sector - Njokwana, Zukiswa (University of the Witwatersrand, Johannesburg, 2024)
South Africa’s economy is heavily reliant on coal-fired power which greatly contributes to greenhouse gas emissions, hence the country’s commitment to shift to renewable energy by 2030 as per the Paris agreement. However, this shift has the potential to leave employees in the coal mining sector uncertain of their jobs, thus, the need to implement the Just Energy Transition (JET) which aims to institute a just and fair transition for coal mining sector employees and affected communities. This research explored implications of the JET for employees in the South African mining energy sector in Mpumalanga province. It assessed employment benefits and challenges of the JET, and also examined forms of organisational employee support for employees in the coal mining sector in South Africa. Ten participants were interviewed and the collected data was analysed using thematic analysis. The data incorporated evidence from participants which revealed that there are employment benefits and challenges of the JET for employees in the coal mining sector in South Africa. The data further exhibited that coal mining sector organisations can play a role in supporting employees in the transition process. In conclusion, the study contributed in revealing the JET implications on the South African coal mining sector employees related to employment benefits and challenges, and organisational support mechanisms. Another revelation is that there is a lack of strong awareness about the JET among employees which implies inadequate organisational communication to employees about the JET. This is a threat to the implementation of a just transition for employees
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Energy Leadership to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Just Energy Transition; Just Transition; Employees; South African coal mining sector; Energy mix; UCTD; SDG-8: Decent work and economic growth; SDG-9: Industry, innovation and infrastructure